(untitled) (Fiep Bulletin - online, 2015)
The research project will be based on the production of scientific knowledge in Physical Education, and as a source of research, the epistemological analysis performed by Gamboa at the University of Brasilia (1982), the State University of Campinas (Unicamp, 1997) and Pontifical Catholic University of Campinas (1996), as well as the work of Silva (1997). As a result in the production of knowledge in the South, we identified the presence of four theoretical and methodological approaches: Empirical-Analytical, Phenomenological-Hermeneutics Research, Postmodern and Critical-Dialectic approach. Was evident in analyzes hegemony of Analytic-Empirical trends in all programs surveyed. Anyway, we hope that this research will stimulate future, further studies to deepen the controversies, identify constraints and stimulate epistemological vigilance in other regions, that were not mentioned here, strengthening, thus, the production of knowledge in other regions of Brazil.